Mini dishwasher machine / Ahmad As-Syaffi Ahmad Misbah ... [et al.] - Ahmad Misbah, Ahmad As-Syaffi; Shahrol Ismail, Zainul Zikry; Md Nor, Muhammad Syazwan; Hosni, Nurul Balqis
Most who use the dishwasher are restaurant or catering workers. This is because they need to wash many plates. Not many people buy this dishwasher for home use because it is so expensive. We make survey to people that what range of price that they would buy the dishwasher machine. After that survey, we can make the dishwasher machine followed the price from that survey. Our dishwasher machine is not same with machine that already exist at the market. From the price, our machine is more affordable to buy. Other than that, our machine look is unique from other machine at the market. The time taken to wash the plate is less than 1 minute per plate. And it is not produce much noise. The material that we use is not same like the exist at the market. We use acrylic to make the body of the part. This is because the acrylic have higher tensile strength and it is also light in weight. Acrylic have many type of color. So that the customer can choose or costume what color that they want for their dishwasher machine